Formation of a colloidal CdSe and ZnSe quantum dots via a gamma radiolytic technique - Salem, Aeshah Nizar; Saion, Elias; Al-Hada, Naif Mohammed; Shaari, Abdul Halim; Mohamed Kamari, Halimah; Soltani, Nayereh; Radiman, Shahidan (MDPI, 2016)
Colloidal cadmium selenide (CdSe) and zinc selenide (ZnSe) quantum dots with a hexagonal structure were synthesized by irradiating an aqueous solution containing metal precursors, poly (vinyl pyrrolidone), isopropyl alcohol, and organic solvents with 1.25-MeV gamma rays at a dose of 120 kGy. The radiolytic processes occurring in water result in the nucleation of particles, which leads to the growth of the quantum dots. The physical properties of the CdSe and ZnSe nanoparticles were measured by various characterization techniques. X-ray diffraction (XRD) was used to confirm the nanocrystalline structure, energy-dispersive X-ray spectroscopy (EDX) was used to estimate the material composition of the samples, transmission electron microscopy (TEM) was used to determine the morphologies and average particle size distribution, and UV-visible spectroscopy was used to measure the optical absorption spectra, from which the band gap of the CdSe and ZnSe nanoparticles could be deduced.